2020
DOI: 10.18474/0749-8004-55.4.437
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Trap Color and Residual Attraction of a Pheromone Lure for Monitoring Stink Bugs (Hemiptera: Pentatomidae)

Abstract: Stink bugs (Hemiptera: Pentatomidae) are commonly monitored using pyramid traps baited with a pheromone. Initially, the pyramid traps were painted yellow and predominantly used to monitor native stink bug species. However, research studies involving the exotic Halyomorpha halys Stål (Hemiptera: Pentatomidae) now use pyramid traps that are black, not yellow. As H. halys moves across the southeastern United States, the use of a single trap, yellow or black, for monitoring and conducting research studies would be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 28 publications
2
7
0
Order By: Relevance
“…Conversely, stinkbugs were not attracted to either trap colour. Although our study had very low numbers of stinkbugs, this result is supported by(Cottrell et al, 2020) who found that BMSB and other stinkbugs are not signi cantly in uenced by trap colour.Our results provide evidence that olfactory cues are clearly more species-speci c than colour for both Psylloidea and Pentatomoidea. This is unsurprising given that previous studies have shown the high sensitivity of olfactory cues, particularly for Psylloidea.…”
supporting
confidence: 85%
See 2 more Smart Citations
“…Conversely, stinkbugs were not attracted to either trap colour. Although our study had very low numbers of stinkbugs, this result is supported by(Cottrell et al, 2020) who found that BMSB and other stinkbugs are not signi cantly in uenced by trap colour.Our results provide evidence that olfactory cues are clearly more species-speci c than colour for both Psylloidea and Pentatomoidea. This is unsurprising given that previous studies have shown the high sensitivity of olfactory cues, particularly for Psylloidea.…”
supporting
confidence: 85%
“…For example, P. a nis was attracted to BMSB lures whether they were in combination with ACP lures or not, and although TPP was repelled by both lure types, combinations of these lures did not increase repellancy signi cantly. Unsurprisingly, we found that over time lure effectiveness declined as the chemical degrades, which has been an identi ed issue for lure longevity (Suckling, 2000); (Cottrell et al, 2020). The impact of the lures were most prominent for all taxa in the rst two weeks, after which TPP was the only insect still detecting and avoiding BMSB lures.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Pheromone needs to be updated in time. If there are too many residual pheromones, it will overwhelm the enlightening information [13]. In other words, after each ant completes a step or completes a cycle, the residual information must be updated.…”
Section: Mathematical Model Of Ant Colony Algorithmmentioning
confidence: 99%
“…In formula (13), ϑ represents the degree of passive stretching of the hind leg muscles corresponding to the angle difference λ b at the knee joint under the shooting take-off, and ζ represents the angle with the hip joint as the axis relative to the horizontal plane.…”
Section: Balance and Stability Control Principle Of Basketball Skillsmentioning
confidence: 99%